PENERAPAN ARSITEKTUR METAFORA PADA SEKOLAH TINGGI TRANSPORTASI DARAT DI JAKARTA - Bayu Tri Nurcahyo; Harfa Iskandaria; Anggraeni Dyah S. (MAESTRO, 2020)
Every year, the land transportation industry in Indonesia has experienced a rapid increase and development, this is marked by an increase in infrastructure such as the construction of roads, toll roads and traffic facilities, specifically the construction of railroads in the country owned by the government, an increase in the number of land transportation as well. Influencing the opening of new routes that are increasingly developing and varied to reach large and small cities. Several means of transportation have also prepared steps, for example, Transjakarta and MRT which have plans to add road routes. The Ministry of Transportation predicts that the current growth in the number of land transport passengers will reach 28.10%. Therefore, with the construction of educational facilities in Jakarta with the concept of Metaphorical Architecture,this concept identifies the relationship between objects but the relationship is more abstract than real and is part of the language style used to explain something through equations and comparisons,which is expected. Can be means of education that triggers the productive generation of Indonesia to join the world of land transportation industry in fulfilling the need for quality and competent education both nationally and internationally as well as meeting the criteria in the specified capabilities and competencies.